1989
DOI: 10.1002/kin.550210805
|View full text |Cite
|
Sign up to set email alerts
|

Thermal decomposition of propyne and allene in shock waves

Abstract: Propyne (p-C3H4) or allene (a-C3H4) mixtures, highly diluted with Ar, were heated to the temperature range 1200-1570 K at pressures of 1.7-2.6 atm behind reflected shock waves. The thermal decompositions of propyne and allene were studied by both measuring the profiles of the IR emission at 3.48 p m or 5.18 pm and analyzing the concentrations of reacted gas mixtures. The mechanism and the rate constant expressions were discussed from both the profiles and the concentrations of reactant and products obtained. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
132
3
1

Year Published

1989
1989
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 143 publications
(147 citation statements)
references
References 25 publications
11
132
3
1
Order By: Relevance
“…at temperatures in the range of 1200-2000 K, thus in quantitative agreement with the experimental values of both Hidaka et al [88,89] and Wu and Kern. [87] The rate constant calculations for dissociation processes showed that the only significant products in this temperature range are C 3 H 3 radicals plus atomic hydrogen; the total rate coefficient for the molecular hydrogen elimination is typically about three orders of magnitude (or more) smaller than that for carbon-hydrogen bond fission.…”
supporting
confidence: 89%
“…at temperatures in the range of 1200-2000 K, thus in quantitative agreement with the experimental values of both Hidaka et al [88,89] and Wu and Kern. [87] The rate constant calculations for dissociation processes showed that the only significant products in this temperature range are C 3 H 3 radicals plus atomic hydrogen; the total rate coefficient for the molecular hydrogen elimination is typically about three orders of magnitude (or more) smaller than that for carbon-hydrogen bond fission.…”
supporting
confidence: 89%
“…To improve our modeling of the formation of acetylene, we have considered the addition of H-atoms to propyne to give acetylene and methyl radicals (reaction 26) in a single step with the rate constant proposed by Hidaka et al [27]. A second channel giving acroleine and H-atoms has been considered for the addition of OH radicals to propyne (reaction 31).…”
Section: Table Imentioning
confidence: 99%
“…g : Rate constant at low pressure limit deduced from the rate constant at low pressure limit proposed by Marinov et al [4] for reaction (27) and from the ratio between the rate constants at high pressure limit of reactions (27) and (28). h : Rate constant of this addition taken equal to that of reaction (30) i : Rate constant estimated as that of the similar reaction in the case of acetylene [20]. j : Rate constant estimated as that of the similar reaction in the case of propene as proposed by Tsang [37].…”
Section: Reactions Of Ac3h4 (Ch2=c=ch2 Allene)mentioning
confidence: 99%
“…According to Hidaka et al [63,64], an effective reaction time (t e ) was defined as the time between the heating of the mixture by the reflected shock wave and the time at which the reflected shock pressure had fallen by 20%. Assuming the adiabatic expansion of a non-reactive mixture, the temperature drops by ≈ 8.5% from its initial value at t e .…”
Section: Pyrolysismentioning
confidence: 99%
“…The pyrolysis experiments of propanal, n-butanal and n-pentanal were performed in a single-pulse magic-hole type shock tube (SPST) (Hidaka et al [62][63][64][65]). The experimental conditions studied are summarized in Table 2.…”
Section: Pyrolysismentioning
confidence: 99%